An electrostatic and probabilistic simulation model to describe neurosecretion at the synaptic scale. (2nd October 2017) - Macias-Medri, A.E.; Liendo, Jacinto A.; Silva, Ricardo J.
ABSTRACT: A hybrid simulation model (macro-molecular dynamics and Monte Carlo method) is proposed to reproduce neurosecretion and exocytosis. A theory has been developed for vesicular dynamics based on quasi–static electric interactions and a simple transition–state model for the vesicular fusion. Under the non–equilibrium electric conditions in an electrolytic fluid, it is considered that the motion of each synaptic vesicle is influenced by electrostatic forces exerted by the membranes of the synaptic bouton, other vesicles, the intracellular and intravesicular fluids, and external elements to the neuron. In addition, friction between each vesicle and its surrounding intracellular fluid is included in the theory, resulting in a drift type movement. To validate the vesicle equations of motion, a molecular dynamics method has been implemented, where the synaptic pool was replaced by a straight angle parallelepiped, the vesicles were represented by spheres and the fusion between each vesicle and the presynaptic membrane was simulated by a Monte Carlo type probabilistic change of state. Density profiles showing clusters of preferential activity as well as fusion distributions similar to the Poisson distributions associated with miniature end–plate potentials were obtained in the simulations.